UNCONSCIOUS STATE ANALYSIS OF CONSCIOUS COMPETENCE LEARNING MODEL BY ABRAHAM MASLOW AS FOUR STAGE OF LEARNING - GP Harianto (Inculco Journal of Christian Education, 2021)
Abstract: Learning difficulties have always been experienced by every student. There are many obstacles so that a person falls into long learning difficulties, whether he realizes it or not. The problem is how to change students from being unconscious in their learning difficulties to becoming conscious, skilled and even professional based on the Conscious Competence Learning Model (CCL) according to Abraham Maslow as Four Stage of Learning? The objective is to answer the following questions: What is the CCL Model? How is the analysis of the unconscious according to the CCL Model? How are the possibilities for developing the unconscious to become a conscious and even increasing the potential in him? Results The CCL model can be used to solve students' unconscious problems in facing learning difficulties. The progress of the CCL model can be seen is: he is unconscious (stage 1) turns into a conscious position to realize his weaknesses and wants to rise above learning difficulties (stage 2), then he has learning competence (in stage 3) and continues learning to become a profession (stage 4). Abstrak: Kesulitan belajar selalu pernah dialami oleh setiap peserta didik. Banyak kendala sehingga seseorang jatuh dalam kesulitan belajaran yang panjang baik disadari maupun tidak disadarinya.  Masalah  adalah  bagaimanakah merubah siswa  dari keadaan Unconscious (keadaan  tak sadar) dalam kesulitan belajarnya menjadi  conscious (sadar), terampil bahkan profesional berdasarkan Model Conscious Competence Learning (CCL) menurut Abraham Maslow sebagai Four Stage of Learning? Tujuan  adalah   menjawab beberapa pertanyaan sebagai berikut: Apakah yang dimaksud dengan Model CCL? Bagaimana analisis keadaan unconscious menurut  Model CCL?  Bagaimanakah kemungkin-kemungkinan mengembangkan unconscious menjadi conscious bahkan dapat meningkatkan potensi dalam dirinya? Hasil Model CCL adalah dapat digunakan untuk menyelesaikan masalah unconscious siswa dalam menghadapi kesulitan belajar. Progress model CCL dapat dilihat adalah: ia  unconscious (tahap 1) berubah menjadi conscious  dalam posisi menyadari kelemahannya dan mau bangkit menerobos kesulitan belajar (tahap 2), kemudian  ia  mempunyai kompeten belajar (tahap 3) dan berlanjut belajar menjadi profesi (tahap 4).